The effect of using organ system board media on IPAS learning outcomes of 5th-grade elementary school - Fahda Bintang Maulidina; Desak Made Darmawati (Inovasi Kurikulum, 2025)
The low learning outcomes of students in the topic of the human digestive system in the IPAS subject of grade 5 at SDN Jatimurni VI Bekasi serve as the background for this study. The use of the organ systems board as a learning medium is proposed to improve students' conceptual understanding and learning outcomes. This study aims to examine the effect of using the the organ systems board media on IPAS learning outcomes of 5th-grade students. The research employed a quantitative method with a quasi-experimental design involving two classes: an experimental class using the organ systems board media and a control class without it. Both groups were given pre-tests and post-tests. The results showed a significant difference in the average learning outcomes between the experimental and control classes. The post-test mean score of the experimental class was higher than that of the control class. It is concluded that the use of the the organ systems board media has a significant positive effect on the IPAS learning outcomes of 5th-grade students at SDN Jatimurni VI Bekasi.   Abstrak Rendahnya hasil belajar peserta didik dalam materi sistem pencernaan manusia pada mata pelajaran IPAS kelas 5 SDN Jaimurni VI Bekasi menjadi latar belakang dalam penelitian ini. Untuk mengatasi permasalahan tersebut, media pembelajaran papan sistem organ diusulkan sebagai solusi untuk meningkatkan pemahaman konsep dan hasil belajar peserta didik. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media papan sistem organ terhadap hasil belajar IPAS peserta didik kelas 5 SDN Jatimurni VI Bekasi. Metode yang digunakan adalah metode kuantitatif dengan desain quasi experimental design yang melibatkan dua kelas, yaitu kelas eksperimen yang menggunakan media papan sistem organ dan kelas kontrol yang tidak menggunakan papan sistem organ. Kedua kelas diberikan instrumen pretest dan post test. Hasil penelitian menunjukkan adanya perbedaan signifikan antara nilai rata-rata hasil belajar kelas eksperimen dan kelas kontrol. Kesimpulan dari penelitian ini adalah bahwa penggunaan media papan sistem organ memberikan pengaruh signifikan terhadap peningkatan hasil belajar IPAS peserta didik kelas 5 SDN Jatimurni VI Bekasi. Kata Kunci: IPAS; hasil belajar; papan sisem organ